1997
DOI: 10.1038/387073a0
|View full text |Cite
|
Sign up to set email alerts
|

Contrast dependence of contextual effects in primate visual cortex

Abstract: The responses of neurons in the visual cortex to stimuli presented within their receptive fields can be markedly modulated by stimuli presented in surrounding regions that do not themselves evoke responses. This modulation depends on the relative orientation and direction of motion of the centre and surround stimuli, and it has been suggested that local cortical circuits linking cells with similar stimulus selectivities underlie these phenomena. However, the functional relevance and nature of these integrative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
429
6
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 479 publications
(474 citation statements)
references
References 25 publications
38
429
6
1
Order By: Relevance
“…A distinct CRF stimulus, in contrast, yielded relief from suppression. Numerous subsequent studies have confirmed these effects (e.g., Cavanaugh et al 2002;Lamme 1995;Levitt and Lund 1997;Li et al 2000;Zipser et al 1996). These results reveal that similar effects occur for luminance contrast polarity.…”
Section: Feature Salience Discriminability and Neuronal Response Mosupporting
confidence: 69%
See 2 more Smart Citations
“…A distinct CRF stimulus, in contrast, yielded relief from suppression. Numerous subsequent studies have confirmed these effects (e.g., Cavanaugh et al 2002;Lamme 1995;Levitt and Lund 1997;Li et al 2000;Zipser et al 1996). These results reveal that similar effects occur for luminance contrast polarity.…”
Section: Feature Salience Discriminability and Neuronal Response Mosupporting
confidence: 69%
“…These responses are often modulated by the copresence of stimuli surrounding the CRF (Allman et al 1985;Blakemore and Tobin 1972;Das and Gilbert 1999;DeAngelis et al 1994;Kapadia et al 1995;Knierim and van Essen 1992;Lamme 1995;Levitt and Lund 1997;Li and Li 1994;Maffei and Fiorentini 1976;Nelson and Frost 1978;Zipser et al 1996). These modulatory effects parallel many well-known examples of the influence of context on visual perception .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…That is, the perceived orientation of the target was shifted towards the orientation of the context bars. Contrast-dependent switching of contextual influences has also been demonstrated by a number of physiological studies (Levitt and Lund 1997;Polat et al 1998;Mizobe et al 2001), but have not, to our knowledge, been reported systematically in a psychophysical setting.…”
Section: Discussionmentioning
confidence: 68%
“…This non classical surround provides input from a larger portion of the visual scene than originally thought, permitting integration of information at early levels in the visual processing stream. Recent works indicate that neuronal surround modulation at cross-orientation, an orientation orthogonal to the preferred orientation of the CRF, play a key role in intermediate-level visual tasks, such as perceptual pop-out [14], contrast facilitation [3,20], and contextual modulation [8,4,5], and could endow neurons with a graded specialization for processing angular visual features such as corners and junctions [18,4].…”
Section: Introductionmentioning
confidence: 99%